A lncRNA to repair DNA. (29th September 2015) - Lukas, Jiri; Altmeyer, Matthias
Abstract : Long non‐coding RNAs (lncRNAs) have emerged as regulators of various biological processes, but to which extent lncRNAs play a role in genome integrity maintenance is not well understood. In this issue of EMBO Reports, Sharma et al 1 identify the DNA damage‐induced lncRNA DDSR1 as an integral player of the DNA damage response (DDR). DDSR1 has both an early role by modulating repair pathway choices, and a later function when it regulates gene expression. Sharma et al 1 thus uncover a dual role for a hitherto uncharacterized lncRNA during the cellular response to DNA damage. Abstract : In this issue of EMBO Reports, Misteli and colleagues show that the lncRNA DDSR1 promotes DNA repair by homologous recombination by sequestering BRCA1 and hnRNPUL1.